3D GEOLOGICAL MODELING OF GEOLOGY AND OREBODY BY GEOSTATISTICAL METHODS FOR Cu-Au PORPHYRITIC DEPOSIT IN THE XYZ PROSPECT, NORTHERN SULAWESI - (NIM : 22115020), FIRDAUS
One of the Cu-Au porphyritic deposits in Indonesia is located in northern arm of Sulawesi. The grade distribution of this porphyritic deposit was intensely controlled by the high temperature of the magmatic-hydrothermal fluid, a porphyritic system typically a facture as the medium of hydrothermal fluid flow. The purpose of this research is to generate a 3D model of metal element distributions as well as the geology and vein intensity of the porphyritic deposit, in order to interpret the hydrothermal fluid flow. The 3D modeling was performed using geostatistical (linear and non-linear) methods with a database obtained from the XYZ prospect area. The exploration drilling data totaled 58 drillhole with a spacing average Ã‚Â± 50 m and average depth of 220 m. The dataset consisted of grade elements (Cu, Au, Ag, Mo, Pb and Zn), lithologies, alteration types, vein intensity and alteration intensity. The 3D modeling of grade elements was performed using Ordinary Kriging (OK), Sequential Gaussian Simulation (SGS) and Indicator Kriging (IK), whereas the 3D modeling of lithologies, alteration types, vein intensity and alteration intensity was performed using IK. Statistical and variogram analyses were used as parameters in the estimation and simulation for each geostatistical methods. Data analysis and interpretation revealed a similarity betwen, the continuous spatial distribution of Cu grade (> 0,20 %) determined by SGS and the model by IK with a cut-off of 0,27 %, These model commonly showed corelation with the pattern of continuous vein intensity and alteration intensity. The lithologic and alteration models established by IK showed that diorite group and potassic zone, which were correlated with the continuous vein intensity and alteration intensity, could be used to indicate the pattern of hydrothermal fluid flow.